1994
DOI: 10.1212/wnl.44.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Creutzfeldt‐Jakob disease

Abstract: We tested DNA from 15 centrally infected cases of iatrogenic Creutzfeldt-Jakob disease (CJD) (dura mater or corneal homografts and stereotactic EEG electrodes), 11 peripherally infected cases (native human growth hormone or gonadotrophin), and 110 control individuals for the presence of mutations in the chromosome 20 amyloid gene. No patient or control had any of the known pathogenic point or insert mutations found in familial disease, but allelic homozygosity at polymorphic codon 129 was present in all but tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(46 citation statements)
references
References 13 publications
1
39
1
5
Order By: Relevance
“…Although not in itself pathogenic, it has been shown to influence susceptibility to iatrogenic and sporadic forms of TSE and to affect age at onset and duration of illness in familial TSE; in association with a pathogenic mutation in codon 178, the entire disease phenotype is altered (5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Although not in itself pathogenic, it has been shown to influence susceptibility to iatrogenic and sporadic forms of TSE and to affect age at onset and duration of illness in familial TSE; in association with a pathogenic mutation in codon 178, the entire disease phenotype is altered (5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…42 -44 Examples are the CCR5 gene for HIV infection, 45 malaria and heterozygosity for sickle cell anemia 46 or variant Creutzfeld -Jakob disease and a Gene -environment interaction A Dempfle et al polymorphism in codon 129 of the prion protein gene PRNP. 47 In these examples, individuals with certain genotypes have a much lower risk for infection or progression to serious disease. Infectious disease studies usually include only individuals at high risk of infection (assumed to be exposed).…”
Section: Study Designs For G â Ementioning
confidence: 99%
“…This polymorphism is a key determinant of susceptibility to sporadic (10) and acquired (8,11) prion diseases and may affect age at onset (12)(13)(14). Based on the analysis of 300 sporadic CJD subjects, Parchi et al (14) identified six distinct clinicopathological variants of sCJD, which appeared to be specified largely by the genotype at codon 129 and the physiochemical properties of PrP Sc .…”
mentioning
confidence: 99%